Study of the Impact of lab-to-Land Programme on Tribal and Non-tribal Participants in Kerala Agricultural University - Sudha V K (Department of Agricultural Extension, College of Horticulture, 1987)
The study was conducted in Trichur district of Kerala State to study the impact of Lab-to-Land Programme on tribal and non-tribal participants in Kerala Agricultural University. The objectives were: 1. To study the perception about Lab-to-Land Programme by participant farmers. 2. To measure the Scientific orientation of the participant farmers of the Programme vis-à-vis non-participant farmers. 3. To study the extent of adoption of technology transferred by participant and non-participant farmers. 4. To study the relationship of selected personal, socio-economic and socio-psychological characters of participants and non-participants with perception about Lab-to-Land Programme by participants, scientific orientation of participants and non-participants, extent of adoption of transferred technology by participants and non-participants. 5. To identify the constraints in the adoption of technology transferred under the Programme by the participants. The study revealed that majority of the non-tribal and tribal participants had higher perception about the programme. With regard to scientific orientation also majority of tribal and non-tribal participants were in high scientific orientation group compared to tribal non-participants and non-tribal non-participants. Also, it was noticed that the extent of adoption of transferred technology was more in participants than non-participants. It was also revealed that there was significant difference in the scientific orientation of participants and non-participants. But no significant difference was noticed between scientific orientation of participant tribals and non-participant tribals. In the case of extent of adoption of transferred technology also, significant difference was noticed between the different groups of participants and non-participants. The study of personal, socio-economic and socio-psychological variables revealed that majority of the participants and non-participants were middle aged. The mean scores for economic motivation, Management orientation, Extension orientation and level of aspiration were found to be higher in both participant tribals and non-tribals than in non-participant tribals and non-tribals. The correlation analysis gave the following results. Income was found to be positively and significantly associated with perception about Lab-to-Land Programme in tribal participants. Economic motivation showed positive and significant relationship with scientific orientation in both participant and non-participant tribals. Economic motivation also showed positive and significant relationship with extent of adoption in both groups of participants and non-participants. Management orientation was found to be positively and significantly associated with scientific orientation of non-tribal participants only. Extension orientation was perception about Lab-to-Land Programme in both group of participants. A positive and significant relationship was observed between extension orientation and extent of adoption of both participants and non-participants. The important constraints perceived by non-tribal participants were inadequacy of capital, non-availability of credit, high cost of feed, uneconomic holding size, lack of good breeds etc. The important constraints perceived by tribal participants were inadequacy of capital, uneconomic holding size, non-availability of credit, poor socio-economic status, lack of knowledge about technology etc.